An introduction to parallel programming - Pacheco, Peter S. (Morgan Kaufmann, 2011)
Author Peter Pacheco uses a tutorial approach to show students how to develop effective parallel programs with MPI, PThreads, and OpenMP. The first undergraduate text to directly address compiling and running parallel programs on the new multi-core and cluster architecture, An Introduction to Parallel Programming explains how to design, debug, and evaluate the performance of distributed and shared-memory programs. User-friendly exercises teach students how to compile, run and modify example programs.
Keywords: Parallel programming (Computer science); elektronické knihy; electronic books